Comparative Chloroplast Genomics of Actinidia deliciosa Cultivars: Insights into Positive Selection and Population Evolution - He, Xiaojing; Yang, Yang; Zhang, Xingya; Zhao, Weimin; Zhang, Qijing; Luo, Caiyun; Xie, Yanze; Li, Zhonghu; Wang, Xiaojuan (International journal of molecular sciences, 2025)
The chloroplast genome, as an important evolutionary marker, can provide a new breakthrough direction for the population evolution of plant species. Actinidia deliciosa represents one of the most economically significant and widely cultivated fruit species in the genus Actinidia. In this study, we sequenced and analyzed the complete chloroplast genomes of seven cultivars of Actinidia. deliciosa to detect the structural variation and population evolutionary characteristics. The total genome size ranged from 156,404 bp (A. deliciosa cv. Hayward) to 156,495 bp (A. deliciosa cv. Yate). A total of 321 simple sequence repeats (SSRs) and 1335 repetitive sequences were identified. Large-scale repeat sequences may facilitate indels and substitutions, molecular variations in A. deliciosa varieties' chloroplast genomes. Additionally, four polymorphic chloroplast DNA loci (atpF-atpH, atpH-atpI, atpB, and accD) were detected, which could potentially provide useful molecular genetic markers for further population genetics studies within A. deliciosa varieties. Site-specific selection analysis revealed that six genes (atpA, rps3, rps7, rpl22, rbcL, and ycf2) underwent protein sequence evolution. These genes may have played key roles in the adaptation of A. deliciosa to various environments. The population evolutionary analysis suggested that A. deliciosa cultivars were clustered into an individual evolutionary branch with moderate-to-high support values. These results provided a foundational genomic resource that will be a major contribution to future studies of population genetics, adaptive evolution, and genetic improvement in Actinidia.